2010
DOI: 10.1093/rheumatology/keq183
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations in patients with immune-mediated inflammatory diseases

Abstract: Patients with immune-mediated inflammatory diseases (IMID) such as RA, IBD or psoriasis, are at increased risk of infection, partially because of the disease itself, but mostly because of treatment with immunomodulatory or immunosuppressive drugs. In spite of their elevated risk for vaccine-preventable disease, vaccination coverage in IMID patients is surprisingly low. This review summarizes current literature data on vaccine safety and efficacy in IMID patients treated with immunosuppressive or immunomodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
0
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 90 publications
2
133
0
16
Order By: Relevance
“…Numerous authors state similar efficiency of vaccination for RA patients and healthy volunteers, without any significant influence of DMARD's or biological therapy on the humoral response (Elkayam 2006;Rahier et al 2010). A few recent studies reported a mild or severe impairment of the humoral response after administration of biological therapy in patients suffering from RA (Gelinck et al 2008;van Assen et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous authors state similar efficiency of vaccination for RA patients and healthy volunteers, without any significant influence of DMARD's or biological therapy on the humoral response (Elkayam 2006;Rahier et al 2010). A few recent studies reported a mild or severe impairment of the humoral response after administration of biological therapy in patients suffering from RA (Gelinck et al 2008;van Assen et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The Advisory Committee on Immunization Practices recommends that adults ages Ն19 years with immunocompromising conditions receive a dose of PCV13 followed by a dose of PPV23 at least 8 weeks later (5). Despite these recommendations, vaccination coverage in RA patients is surprisingly low (25-30%), mainly because of a lack of awareness by health care professionals and a distrust in the safety and efficacy of vaccines (6,7). Concerns about safety are not justified.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with autoimmune disorders starting anti-TNF-␣ antagonists, immunomodulators, or corticosteroid drugs are at risk of a serological nonresponse, of the development of a major adverse event, or of an exacerbation of their autoimmune disease (17,18). Guidelines recommend that patients at risk for complication of influenza, including those treated with anti-TNF-␣ drugs, should be vaccinated annually against influenza (19).…”
mentioning
confidence: 99%
“…Guidelines recommend that patients at risk for complication of influenza, including those treated with anti-TNF-␣ drugs, should be vaccinated annually against influenza (19). Usually, patients are required to be on a stable drug treatment before the vaccination is provided, but data on the effect of anti-TNF-␣ antagonists on immunogenicity and the response to influenza vaccination are scarce (17,18). A few recent studies reported that patients treated with anti-TNF-␣ drugs reach an adequate immunoprotective response against influenza after vaccination, although antibody titers and cellular response rates are lower than those of similar patients not treated with anti-TNF-␣ and healthy controls (20)(21)(22).…”
mentioning
confidence: 99%